Short-term and long-term forecasting of ecological capacity of civil aviation airports - Кажан, К.І. (Proceedings of National Aviation University (archive), 2009)
Impact of the main environmental factors – noise and air pollution – on the environmental capacity of civil aviation airports was investigated in the article. The method of environmental capacity forecasting taking into account opportunity of definition of optimal aircraft fleet and airport development scenarios was proposed.